2018
DOI: 10.1074/jbc.ra117.000834
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of ferroportin in murine myeloid cells increases iron accumulation and stimulates osteoclastogenesis in vitro and in vivo

Abstract: Osteoporosis, osteopenia, and pathological bone fractures are frequent complications of iron-overload conditions such as hereditary hemochromatosis, thalassemia, and sickle cell disease. Moreover, animal models of iron overload have revealed increased bone resorption and decreased bone formation. Although systemic iron overload affects multiple organs and tissues, leading to significant changes on bone modeling and remodeling, the cell autonomous effects of excessive iron on bone cells remain unknown. Here, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 88 publications
1
33
0
Order By: Relevance
“…In addition, we believe that tightly regulated iron donation by Mɸs is a critical piece of this repair-to-resolution process. Indeed, loss of Mɸ iron donation delays or impairs wound healing in mice (64,65,83). Thus, we propose that Mɸs continually supply iron to cells undergoing repair until cell regeneration/ repair is completed or near completion.…”
Section: Proposed Model For Iron-cycling Mɸs In the Regulation Of Tismentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, we believe that tightly regulated iron donation by Mɸs is a critical piece of this repair-to-resolution process. Indeed, loss of Mɸ iron donation delays or impairs wound healing in mice (64,65,83). Thus, we propose that Mɸs continually supply iron to cells undergoing repair until cell regeneration/ repair is completed or near completion.…”
Section: Proposed Model For Iron-cycling Mɸs In the Regulation Of Tismentioning
confidence: 93%
“…Resident Mɸs are indispensable for bone remodeling, as evidenced by the well-studied population of osteoclasts that drive bone resorption. Iron is implicated in the regulation of osteoclast function, such that iron release via Fpn is necessary for normal osteoclastogenesis and global skeletal homeostasis in mice (83). For instance, mice that lack Fpn activity in osteoclasts have accelerated osteoclastogenesis and skeletal resorption.…”
Section: Tissue Mɸs Regulate Iron Homeostasis and Tissue Functionmentioning
confidence: 99%
“…The amount of non-mitochondrial oxygen consumption was determined by inhibiting the respiratory chain activity with an antimycin A and rotenone cocktail (10 µM). These data were used to calculate the mitochondrial basal respiration, ATP-linked respiration, reserve respiratory capacity, and proton leak as we previously described 34,35 .…”
Section: Methodsmentioning
confidence: 99%
“…Generation of mice with conditional deletion of Slc40a1 in the macrophage-osteoclast lineage using LysMCre mice was consistent with in vitro data and resulted in a phenotype of increased bone mass and strength (Figure 5 and figure supplement 4). Thus, Slc40a1 regulates bone structure and strength via direct actions in the macrophage-osteoclast lineage, further supporting the conclusion that MMnet plays a key role in the physiological regulation of bone mass by osteoclasts.Nevertheless, Wang and colleagues(Wang et al, 2018) recently reported that deletion of Slc40a1 in the myeloid lineage using LysMCre mice causes decreased bone mass and mineralisation in female, but not male, mice. Wang et al also reported that deletion of Slc40a1 in terminally differentiated osteoclasts using CtskCre mice resulted in no skeletal abnormalities in either sex.…”
mentioning
confidence: 99%